THE STARTUP RETENTION DILEMMA: EXAMINING THE INFLUENCE OF COMPENSATION AND ORGANIZATIONAL CULTURE ON TURNOVER INTENTION THROUGH THE MEDIATION OF JOB SATISFACTION - Rohman, Abdul; Parimita, Widya (Fakultas Ekonomi dan Bisnis Universitas Tanjungpura, 2023)
Turnover intention refers to an employee